2021
DOI: 10.3390/s21144736
|View full text |Cite
|
Sign up to set email alerts
|

Deep Transfer Learning Based Intrusion Detection System for Electric Vehicular Networks

Abstract: The Controller Area Network (CAN) bus works as an important protocol in the real-time In-Vehicle Network (IVN) systems for its simple, suitable, and robust architecture. The risk of IVN devices has still been insecure and vulnerable due to the complex data-intensive architectures which greatly increase the accessibility to unauthorized networks and the possibility of various types of cyberattacks. Therefore, the detection of cyberattacks in IVN devices has become a growing interest. With the rapid development … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(38 citation statements)
references
References 52 publications
2
36
0
Order By: Relevance
“…Mehedi et al suggested an IDS model based on deep migration learning with IVN, claiming the IDS was equivalent to a number of other current models. Compared to several other current models, its performance is superior 22 . Fernando 23 proposed a class rebalancing strategy based on a class balancing dynamic weighted loss function for the problem of uneven distribution of network attacks, claiming that experiments conducted using this method on highly unbalanced data demonstrated robust generalization, but the method did not include machine learning.…”
Section: Related Workmentioning
confidence: 97%
“…Mehedi et al suggested an IDS model based on deep migration learning with IVN, claiming the IDS was equivalent to a number of other current models. Compared to several other current models, its performance is superior 22 . Fernando 23 proposed a class rebalancing strategy based on a class balancing dynamic weighted loss function for the problem of uneven distribution of network attacks, claiming that experiments conducted using this method on highly unbalanced data demonstrated robust generalization, but the method did not include machine learning.…”
Section: Related Workmentioning
confidence: 97%
“…The experiments use two datasets of the public dataset AWID [ 18 ] and they achieve 96% detection accuracy, improving traditional schemes up to 8%. In the same area, but with a different objective, to speed up the training process, Mehedi et al [ 19 ] propose a deep-TL-based ID model to classify normal traffic and attacks. The TL model makes use of two CNNs and the datasets used for the source and target domain are two different subsets of the new-generation labeled dataset for in-vehicle network [ 20 ], which considers three different types of attacks: flooding, fuzzing, and spoofing.…”
Section: Related Workmentioning
confidence: 99%
“…There are special protocols that facilitate the functioning of IVNs. These protocols include the controller area network (CAN), FlexRay, and Ethernet [ 3 ]. CAN is the most common network topology used for controlling the automotive and the industrial system.…”
Section: Introductionmentioning
confidence: 99%